Cost-Effective and Energy-Efficient Techniques for Underwater Acoustic Communication Modems - Zia, Muhammad Yousuf Irfan (UMA Editorial, 2021)
Underwater wireless sensor networks (UWSNs) are widely used in many applications related to ecosystem monitoring, and many more fields. Due to the absorption of electromagnetic waves in water and line-of-sight communication of optical waves, acoustic waves are the most suitable medium of communication in underwater environments. Underwater acoustic modem (UAM) is responsible for the transmission and reception of acoustic signals in an aquatic channel. Commercial modems may communicate at longer distances with reliability, but they are expensive and less power efficient. Research modems are designed by using a digital-signal-processor (DSP is expensive) and field-programmable-gate-array (FPGA is high power consuming device). In addition to, the use of a microcontroller is also a common practice (which is less expensive) but provides limited computational power. Hence, there is a need for a cost-effective and energy-efficient UAM to be used in budget limited applications. In this thesis different objectives are proposed. First, to identify the limitations of state-of-the-art commercial and research UAMs through a comprehensive survey. The second contribution has been the design of a low-cost acoustic modem for short-range underwater communications by using a single board computer (Raspberry-Pi), and a microcontroller (Atmega328P). The modulator, demodulator and amplifiers are designed with discrete components to reduce the overall cost. The third contribution is to design a web based underwater acoustic communication testbed along with a simulation platform (with underwater channel and sound propagation models), for testing modems. The fourth contribution is to integrate in a single module two important modules present in UAMs: the PSK modulator and the power amplifier.
Finally, the modem developed has been tested experimentally in laboratory (aquatic environment) showing that can communicates at different data rates (100..1200 bps) compared to state-of-the-art research modems. The software used include LabVIEW, MATLAB, Simulink, and Multisim (to test the electronic circuit built) has been employed.
Keywords: Modems - Tesis doctoriales; Acústica submarina - Tesis doctorlaes; Sistemas de telecomunicaciones - Tesis doctoriales; UWSN; Acoustic modem; Class-D amplifier; PWM; Power efficiency